Analysis of Rawa Pening Lake Morphometric Changes for Identification of Land Arises - Nurhadi Bashit; Bandi Sasmito; Fadillah Qur Ani; Abdi Sukmono (Jambura Geoscience Review, 2023)
Rawa Pening Lake is a natural lake with the status of a critical lake in Indonesia because there is an uncontrolled population of water hyacinths, so a layer of water hyacinths covers the surface of the water. Sedimentation causes indications of the appearance of soil to arise. Based on this, it is essential to monitor the presence of surface soil. This study aimed to determine changes in the morphometry and morphology of Rawa Pening Lake, to study changes in morphology, and the spatial distribution of land arising indicative of Rawa Pening Lake. The study This data used the satellite imagery of Landsat 5 in 1989, Landsat 7 in 2002, and Landsat 8 in 2015 and 2021. The method used is NDWI (Normalized Difference Water Index) and manual interpretation to distinguish between water and non-water areas. The results showed that the use of the NDWI method was not optimal for determining the firm boundaries of the lake. The manual interpretation method shows that in 1989–2002, Rawa Pening Lake experienced a narrowing with a change in the area of 75,639 Ha and the distribution of indicative raised land of 141,146 Ha. From 2002–2015, the lake experienced an increase in the area of 159,734 Ha, and the total area of indicative arising land distribution was 99,285 Ha, and in 2015–2021 there was a change in the area of 230,192 Ha with the distribution of raised land of 18.010 Ha.